Peran Pendidikan Karakter dalam Pembentukan Sikap Sosial Remaja di SMA Plus Al-Matholi - Vevi Putri (CV. Lentera Literasi Indonesia, 2026)
This study aims to describe the role of character education in the formation of adolescent social attitudes at Al-Matholi Plus High School. The research method used is qualitative descriptive with a field research approach. The data source was obtained through interviews, observations, and documentation of the Principal, Deputy Head of Curriculum, and 1 teacher of SMA Plus Al-Matholi. The results of the study show that character education has an important role in shaping students' personalities and social attitudes, especially in fostering empathy, responsibility, and cooperation. The implementation of character education is carried out through curriculum, extracurricular activities, and daily interactions in the school environment. The main supporting factors include teacher examples, family support, and student motivation, while the obstacles found include the negative influence of digital media, low interest in learning, and student apathy. Overall, character education has proven to be effective in shaping positive social attitudes of adolescents, noting the need for synergy between schools, families, and communities to achieve optimal results.